1986
DOI: 10.1002/eji.1830160210
|View full text |Cite
|
Sign up to set email alerts
|

Human B cell activation: Selective sensitivity of the early stages to calcium channel‐blocking drugs

Abstract: The importance of Ca2+ in the early events of lymphocyte activation has been suggested by several studies. We examined the effect of calcium channel-blocking drugs (verapamil and nitrendipine) on the progression of human B cells through their activation cycle. Our results show that these drugs suppress the anti-mu-induced human B cell proliferation and interfere with the early events of the B cell activation in a dose-dependent fashion. This suppression correlates with a marked decrease in anti-mu-induced 45Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…However, since EBV-containing SN and not purified virus were used, the possibility that the initial rise in [Ca2+]i could be due to another component than the viral particle itself cannot be ruled out. This possibility is supported by the fact that an anti-CD21 mAb only partially blocks the early increase in [Ca2+]i induced by the addition of EBV-containing SN [28]. It should be stressed that under our experimental conditions the anti-CD21 mAb had no effect by itself on B cell activation (data not shown and P81) * quin-2, as indicated by two lines of evidences: (a) the [Ca2+], increase related to an influx of extracellular Ca2+ is not transient but sustained (always observable after 30 min) and (b) similar results were obtained using indo-1 (data not shown), which presented a lower buffering capacity than quin-2 [36].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, since EBV-containing SN and not purified virus were used, the possibility that the initial rise in [Ca2+]i could be due to another component than the viral particle itself cannot be ruled out. This possibility is supported by the fact that an anti-CD21 mAb only partially blocks the early increase in [Ca2+]i induced by the addition of EBV-containing SN [28]. It should be stressed that under our experimental conditions the anti-CD21 mAb had no effect by itself on B cell activation (data not shown and P81) * quin-2, as indicated by two lines of evidences: (a) the [Ca2+], increase related to an influx of extracellular Ca2+ is not transient but sustained (always observable after 30 min) and (b) similar results were obtained using indo-1 (data not shown), which presented a lower buffering capacity than quin-2 [36].…”
Section: Discussionmentioning
confidence: 89%
“…Correspondence: Bernard [28]. In the present work, the respective contribution of the extra-and intracellular pools of Ca2+ in the increase in [Ca2+]i was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Initial evidence for the presence of L-type Ca 2ϩ channels in lymphocytes relied on pharmacological studies using antagonists of these channels. A number of studies showed effects of these antagonists on B and T cell activation (21)(22)(23)(24). However, the drugs were used at higher concentrations than those used to block authentic voltage-gated Ca 2ϩ channels.…”
mentioning
confidence: 99%
“…Phosphoinositides are well known as substrates for phospholipase C, and thus as precursors of the second messengers inositol trisphosphate and diacylglycerol (reviewed by Berridge, 1985). It was recently reported that the herpes virus Epstein-Barr virus induces protein kinase C activation, probably through phospholipase C activation (Dugas et al, 1988). The human immunodeficiency virus (HIV)-1 glycoprotein gp120 can induce increased levels of inositol trisphosphate in CD4-positive lymphocytes (Kornfeld et al, 1988).…”
Section: Introductionmentioning
confidence: 99%